Utilização de resíduos de poliuretano expandido na moldagem por injeção de compósito de matriz de polietileno de alta densidade - Teixeira, André Luiz (2017)
For a few years now polymeric materials have been ever present around the whole globe. Polyurethane (PU) for example is the sixth most produced polymer globally, generating with that a considerable amount of scrap due to industrialization processes, usage or end of its life cycle. About this, the present dissertation proposes to reprocess industrially discarded PU through mechanical recycling and injection molding to validate reusing this waste, reducing the amount sent to landfill. In order to do that PU scrap was physically mixed with high density polyethylene (HDPE), a commodity polymer, in pellets. PU was obtained from industrial waste of an earplug production process and HPE was bought in local market. PU scrap was obtained as a polymeric blanket that was later milled and micronized. Three different mixtures were manually prepared and placed into an industrial scale injection molding machine which resulted in the production of test specimens of 2%, 5% and 7% in mass of micronized PU into a HDPE matrix. Test specimens were submitted to flexural, tension and impact testing and the results were compared to the properties of 100% virgin specimens and with literature data. The samples indicated that adding PU decreased impact resistance but kept the performance on flexural and tension strengths, even increasing maximum deformation. Regarding thermal properties, the studied material presented the same melt and crystallization temperatures results for Differential Scanning Calorimetry (DSC) as well as loss and storage modulus for Dynamic Mechanical Thermal Analysis (DMTA). Thermogravimetric analysis (TGA) showed a decreased to the mass loss peak temperature when PU percentage increased. Nonetheless, considering all mechanical and thermal properties analyzed, present study shows that reusing the PU scrap is a viable option, given the appropriate process conditions.